Magnetic field distribution in plasma shield during high-power plasma stream target interaction - Chebotarev, V.V.; Garkusha, I.E.; Makhlaj, V.A.; Mitina, N.I.; Solyakov, D.G.; Tereshin, V.I.; Trubchaninov, S.A.; Tsarenko, A.V.; Wuerz, H. (Вопросы атомной науки и техники, 2000)
The distributions of magnetic field in the shielding plasma layers, created during the powerful plasma stream interaction with the graphite sample were carried out. Plasma streams, generated by plasma accelerator QSPA Kh- 50, irradiated graphite targets of 5,13 and 22cm in diameter in longitudinal magnetic field of strength up to 0.54 T. It was shown that distributions of the magnetic field in front of sample were strongly depended on the target diameter. The value of magnetic field displacement from the target plasma was increased with decreasing the target diameter (the magnetic field displacement achieved 0.135T for the target diameter of 5 cm and 0.46 T the target with diameter of 22 cm). The size of the shielding layer in radial direction was determined by a flow of plasma stream around the target.